Supporting The Work of Ed Clinicians: Assessment of A Novel Emergency Department Information System in A Clinical Simulation Center. Issue 1 (June 2015) - Mcgeorge, Nicolette M.; Hegde, Sudeep; Guarrera-Schick, Theresa K.; Lavergne, David T.; Clark, Lindsey N.; Hernandez, Angelica; Benda, Natalie C.; Wears, Robert L.; Perry, Shawna J.; Het-Tinger, A. Zachary; Fairbanks, Rollin J.; Bisantz, Ann M.
There has been momentum to quickly develop health information technology (IT), but these developments may not result in the expected benefits if the IT is not designed to support caregivers. This research aimed to create an interface for emergency department tracking and control using cognitive systems engineering methods. Comparison of the novel displays with currently in-use display designs in a clinical simulation center demonstrated that the novel displays better support the work of providers without increasing workload.